Codes and control: explicating pedagogic communication in classroom practice. Issue 3 (3rd July 2022) - Nolan, Ursula; Mac Ruairc, Gerry
ABSTRACT: The impact of State policy to combat educational disadvantage with two iterations of DEIS supports has had a positive influence the patterns of achievement among all social groups with some notable improvements across a range of indicators for students in DEIS schools. Notwithstanding these improvements, research and evaluations continue to identify a persistent achievement gap for large numbers of working-class students compared to their more middle-class peers. Research evidences the inextricable links between class, economic circumstances, and student outcomes. In producing these more system-oriented data, the dynamism of underlying processes that produces these outcomes can be often masked. Student-teacher characteristics and classroom interactions become variables or aggregated performance datasets, rather than signifiers to unpack the mechanisms of how students and teachers construct their classroom world. Pedagogic communication, so central to classroom teaching and learning, is largely unexplored from the perspective of its construction, transmission, acquisition, context and how these are framed by structures of social relationships. This paper intends to explicate a core component of the student/school relational domain by examining specifically the patterns of pedagogic communication that frame teaching and learning in one case study school located in a very marginalised and challenging community in Ireland. The findings are stark. Different linguistic strategies for engaging in pedagogic communication are detailed in the data but in all cases, they fail to lead to rich learning experiences and positive student outcomes.